2017
DOI: 10.1038/s41598-017-02761-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Networks derived from Breast Cancer Stem Cells control the immune response in the Basal subtype

Abstract: Breast cancer is the most common cancer in women worldwide and metastatic dissemination is the principal factor related to death by this disease. Breast cancer stem cells (bCSC) are thought to be responsible for metastasis and chemoresistance. In this study, based on whole transcriptome analysis from putative bCSC and reverse engineering of transcription control networks, we identified two networks associated with this phenotype. One controlled by SNAI2, TWIST1, BNC2, PRRX1 and TBX5 drives a mesenchymal or CSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…We identified genes that were differentially co-expressed between tumors with high and low infiltrating lymphocyte scores-most of these had already been associated with cancer immunity through other studies [170][171][172][173]. Of particular interest were CXCL13, BTLA, IL7R, LAMP3, and LTB as these genes have been linked to the presence of tertiary lymphoid structures (TLS) and high endothelial venules (HEV) within tumors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified genes that were differentially co-expressed between tumors with high and low infiltrating lymphocyte scores-most of these had already been associated with cancer immunity through other studies [170][171][172][173]. Of particular interest were CXCL13, BTLA, IL7R, LAMP3, and LTB as these genes have been linked to the presence of tertiary lymphoid structures (TLS) and high endothelial venules (HEV) within tumors.…”
Section: Resultsmentioning
confidence: 99%
“…High levels of these two antigens have been linked to an overall better prognosis of patients with breast cancer [175,176]. The same is true for BCL11B, IKZF3, and KLRC4, which have very recently been linked to a prognostic immunogenic signature of triple-negative breast cancers [173,177]. Liu et al [177] found that almost all populations of immune cells, immune system pathways, and their genes were enriched in TNBC compared to both normal samples and other breast cancer subtypes.…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 98%
See 1 more Smart Citation
“…The CSC populations of many solid tumors are identified by the expression of specific cell surface markers, such as CD44 1 CD24 2 in breast cancer [5]. Additionally, increased aldehyde dehydrogenase (ALDH) activity as measured by the Aldefluor assay is used to identify the CSCs of many tumors, including breast [6,7], colon [8], liver [9], lung [10], prostate [11], glioblastoma [12], melanoma [13], and head and neck [14]. The resistance of CSCs to conventional treatments suggests they may mediate the incomplete response to a Departments of Pathology, b Microbiology and Immunology, c Psychology and Neuroscience, and chemotherapy and radiation, and contribute to recurrence [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Breast carcinoma (BC) is the most prevalent cause of cancerrelated mortality in women worldwide (1,2), both in low-and middle-income countries and approximately 1.67 million new cancer cases were diagnosed in 2012 (25% of all cancers) (3). At present, the treatment of breast cancer mainly involves surgery, radiotherapy and chemotherapy; 75% of patients with breast cancer require radiotherapy.…”
Section: Introductionmentioning
confidence: 99%